PELAKSANAAN PELAYANAN PESERTA PROGRAM JAMINAN KESEHATAN MASYARAKAT DI PUSAT KESEHATAN MASYARAKAT DI KELURAHAN TANJUNG HULU KECAMATAN PONTIANAK TIMUR - Purwasih E.01107106, Nyemas Nurdayanti (FISIP Universitas Tanjungpura, 2013)
Regarding the implementation of the service of public health insurance program participants in community health centers regarding ease the service process, the service process openness, speed of service, Equity Services, Leisure Services. This study used qualitative methods and do pendeskriptifan in depth, as well as the methods used to help the research is done by observation, interview guides and documentation. The results of this study found that dissatisfaction regarding the problem here is the attitude of officers and timeliness in providing less care to maintain a working relationship so that it appears unfair service. The point of care provided to people who have a certain status in priority over the common people, while the relatively weak economy is always neglected in favor in service delivery and lack of availability of health centers is one of the supporters of the service process is going well and smoothlyKeywords : service delivery, simpility service, speed of service, disclosure service, fairness in service